Explanation:
2x + y = 12 equ 1
x - y = 9 equ 2
from equ 2 make x the subject
x - y = 9
x = 9 + y equ 3
substitute equ 3 to equ 1
2x + y = 12
2(9 + y ) + y = 12
18 + 2y + y = 12
3y = - 6
y = -2
substitute y = -2 into equ 3
x = 9 + (-2)
x = 9 - 2 = 7
(x, y) = (7, -2)
let's prove and see if we are correct
2x + y = 12
input the values of (x, y) = ( 7, -2) into the question
2(7) + (-2) = 12
14 - 2 = 12
12 = 12
for the second equation
x - y = 9
Input the values of (x, y) = ( 7, -2) into the question
7 - (-2) = 9
7 + 2 = 9
9 = 9